Silver-doped strontium niobium cobaltite as a new perovskite-type ceramic membrane for oxygen separation - Zhang, Z.; Xu, X.; Zhang, J.; Chen, D.; Zeng, D.; Liu, Shaomin; Zhou, W.; Shao, Zongping (Elsevier BV, 2018)
In this work, we report the silver doping as a novel strategy for developing single-phase mixed conducting ceramic membranes with perovskite-type structure for the efficient oxygen separation from air. Specifically, perovskite-type oxide with a nominal composition of Sr0.95Ag0.05Co0.9Nb0.1O3-d(SANC) was designed, synthesized and investigated, and a comparative study with the Ag-free SrCo0.9Nb0.1O3-d(SNC) perovskite-type membrane was also conducted. The incorporation of silver into the perovskite lattice of SNC has been confirmed even after the sintering at 1175 °C using Ag2O as the silver source. An improved sintering feature, enhanced mechanical strength, and an increased electrical conductivity of the SANC membrane when compared to the Ag-free SNC have been observed. Furthermore the chemical bulk diffusion and surface exchange coefficients increased through the silver doping. Above all higher oxygen permeation fluxes were achieved for the SANC membrane when compared with the SNC membrane under the corresponding conditions. Therefore, SANC turned out to be a highly promising ceramic membrane material for oxygen separation.